Nutcracker syndrome, conservative approach: a case report. Issue 10 (23rd October 2022) - Muheilan, Muheilan; Walsh, Anna; O'Brien, Frank; Tuite, David
Abstract: The nutcracker phenomenon (NCP) refers to the compression of the left renal vein, most commonly between the aorta and the superior mesenteric artery (SMA). Nutcracker syndrome (NCS) should be limited to patients who present with the characteristic clinical signs and symptoms alongside diagnostic imaging of the anatomy associated with the syndrome. We report a case of NCS presenting with painless visible hematuria and left flank pain. Imaging showed a left renal vein stenosis at the origin of the SMA with collateralization. Diagnosis of NCP is made by a variety of imaging techniques; approaches to the treatment of NCS include conservative methods, open surgical, laparoscopic or endovascular techniques. Correlation with symptoms, laboratory results and excluding other causes continues to be important in the workup of NCS. Collaboration with the establishment of an International Consortium database will aid in the understanding of this rare disease.